2017
DOI: 10.1038/ncomms14337
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic heat stress and HSF-1 induce autophagy to improve survival and proteostasis in C. elegans

Abstract: Stress-response pathways have evolved to maintain cellular homeostasis and to ensure the survival of organisms under changing environmental conditions. Whereas severe stress is detrimental, mild stress can be beneficial for health and survival, known as hormesis. Although the universally conserved heat-shock response regulated by transcription factor HSF-1 has been implicated as an effector mechanism, the role and possible interplay with other cellular processes, such as autophagy, remains poorly understood. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
190
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(215 citation statements)
references
References 70 publications
14
190
0
Order By: Relevance
“…In poikilotherms, autophagy has been found to help Caenorhabditis elegans survive heat stress (Kumsta et al . ), but a study on D. melanogaster showed a negative effect of autophagy caused by fasting on resisting cold stress (Le Bourg & Massou, ). The present study revealed that activation of autophagy due to fasting is an important mechanism of fish to resist cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…In poikilotherms, autophagy has been found to help Caenorhabditis elegans survive heat stress (Kumsta et al . ), but a study on D. melanogaster showed a negative effect of autophagy caused by fasting on resisting cold stress (Le Bourg & Massou, ). The present study revealed that activation of autophagy due to fasting is an important mechanism of fish to resist cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi experiments were performed as described in (31). The HSF-1 overexpression strain EQ87, hsf-1p::hsf-1::gfp + rol-6, was used for HSF-1 overexpression studies (32,33).…”
Section: Hsf-1 Rnai and Overexpressionmentioning
confidence: 99%
“…Since modulation of autophagy has been found to be essential in many long-lived paradigms, we questioned whether ehbp-1-mediated lipophagy and ER remodeling was a critical contributor of lifespan extension in other long-lived models (Kumsta et al, 2017). Nematodes with mutations in the insulin receptor, daf-2, live significantly longer than wild type controls (Kenyon et al, 1993).…”
Section: A Lipophagy Complex Mediates Cerm Formation and Lipid Turnovmentioning
confidence: 99%